PENGARUH KEPEMILIKAN INSTITUSIONAL, RISK MANAGEMENT COMMITTEE DAN INTELLECTUAL CAPITAL TERHADAP MANAJEMEN LABA - Alfikih, Galih Ikraam; Widiyati, Dian (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
In the face of economic growth and increasingly intense market competition, the business sector, especially industry, is required to adapt and manage performance effectively. The study aims to analyze the influence of institutional ownership, Risk Management Committee, and Intellectual Capital on Earnings Management. The research was carried out by analyzing the financial reports of companies in the industrial sectors listed on the Indonesian Stock Exchange during the period 2018 - 2022. The sample in this study 10 companies of the industry sectors that were listed in the Indonesia Stock Exchange over the period of 2018 - 2022 with purposive sampling technique. The data on this research is secondary data of the company's financial report that has been used as a sample of the research. The variables in this study are Institutional Ownership, Risk Management Committee, and Intellectual Capital as well as Earnings Management.Analysis of research results using EViews 10 software. The research results show that the best model is the Common Effect Model (CEM).The results of this study show that simultaneously Institutional Ownership, Risk Management Committee and Intellectual Capital have an influence on Earnings Management, Institutional Ownership has a influence upon Earnings Management, the Risk Management Committee has no influence over Earnings Management, Intellectual Capital has no influence over Earnings Management.